2008
DOI: 10.1007/s11664-008-0459-7
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Response Time Measurements in Hg0.7Cd0.3Te MWIR Avalanche Photodiodes

Abstract: The response time of front-sided illuminated n-on-p Hg 0.7 Cd 0.3 Te electron avalanche photodiodes (e-APDs) at T = 77 K was studied using impulse response measurements at k = 1.55 lm. We measured typical rise and fall times of 50 ps and 800 ps, respectively, at gains of M % 100, and a record gainbandwidth (GBW) product of GBW = 1.1 THz at M = 2800. Experiments as a function of the collection width have shown that the fall time is strongly limited by diffusion. Variable-gain measurements showed that the impuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…. High avalanche gain (~10 4 ) at low reverse bias, low excess noise factor (F~1), high gain bandwidth product (GBW) ~2.1 THz and very short integration time~ 70 ps make HgCdTe APD to be suitable for low optical signal and high speed applications 47,53 . It can be used in the active gated 2D or 3D mode for identification of targets 57 .…”
Section: Ii-vi Materials Based Apdsmentioning
confidence: 99%
See 3 more Smart Citations
“…. High avalanche gain (~10 4 ) at low reverse bias, low excess noise factor (F~1), high gain bandwidth product (GBW) ~2.1 THz and very short integration time~ 70 ps make HgCdTe APD to be suitable for low optical signal and high speed applications 47,53 . It can be used in the active gated 2D or 3D mode for identification of targets 57 .…”
Section: Ii-vi Materials Based Apdsmentioning
confidence: 99%
“…However, they reported that the planar APD structure provides fill factor~ 100 % and the collection efficiency > 90%, whereas HDVIP diode has advantage to yields low dark current, high quantum efficiency and high operability. 39,47 . They are first to measure the impulse response time for front side illuminated n-on-p MWIR HgCdTe e-APD at 77 K with λ = 1.55 μm laser pulse 47 .…”
Section: Development Of Hgcdte Based Apd Device Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The exclusive electron multiplication in MCT APDs is a major advantages, as it implies that only one transit time needs to be accounted for each type of carriers. Hence, the gain do not directly influence the transit time why ultra-high gain bandwidth products can be achieved in theses detectors [5,6,7]. The highest measured bandwidth of 800 MHz for M=100 is thought to be limited by impedance miss-match in the inter-connexion circuit used to enable a backside illumination of the diode [7].…”
Section: Introductionmentioning
confidence: 99%